Effect of water absorption and curing period on strength and porosity of triple blended concrete. (2021) - Kumar, Mavoori Hitesh; Macharyulu, Ippilli Saikrishna; Ray, Tanushree; Mohanta, Nihar Ranjan; Jain, Mayank; Samantaray, Sandeep; Sahoo, Abinash
Abstract: Water absorption and porosity are the two main factors which are directly related to strength and durability property of concrete. The present work is mainly focused on the influence of water absorption on the compressive strength and effect of curing period on porosity, investigated on concrete specimens triple blended with fly ash, egg shell powder and steel fibres. Fly ash and waste egg shell powder are being used as one of raw material in concrete. In addition to both, a small amount of steel fibers is also added to examine the change in the properties of concrete. Fly ash and egg shell powder are used as a substitution in place of cement in various proportions and initially the experiments were performed to examine the results, with 0%, 0.25%, 0.5% and 0.75% addition of steel fibres by volume of concrete, after 7 days and 28 days of curing period. It is observed that water absorption percentage decreased with the rise in the amount of steel fibers and porosity decreased with the increase in curing period but increased with the rise in the amount of steel fibers. It was also confirmed that a combined mix of 35% fly ash, 6% egg shell powder reinforced with 0.75% steel fibers exhibited the maximum compressive strength.